ELECTROCORTICOGRAPHY-BASED BRAIN COMPUTER INTERFACE FOR PEDIATRIC PATIENT: CHALLENGE ON THE HORIZON - Abdi - Reza (Fakultas Kedokteran Universitas Islam Al-Azhar, 2019)
Electrocorticography-based brain computer interface has accepted recognition as modality connecting human brain to computer device for its signal recording excellence and stability. Implantation for medical purpose has welcomed this modality for bypassing existing nervous system and natural organ to create alternative solution towards previously-unsolved medical problems. Clinical trials have already initiated for Electrocorticography-based BCI implantation in adult. Therefore, bridging a direct brain to computer connectivity in pediatric patient should also become possible. However, several characteristics has made Electrocorticography-based BCI for pediatric patient more complex and should await for further technical solution rather than its adult counterparts. Penghubung otak-komputer berbasis elektrokortikografi telah diakui sebagai metode menghubungkan sinyal otak langsung ke komputer dengan kualitas dan stabilitas perekaman sinyal yang andal. Sinyal otak yang dihubungkan langsung ke komputer dapat memberikan pertolongan bagi pasien dengan kelumpuhan oleh berbagai sebab. Uji penerapan klinis dengan implantasi penghubung otak-komputer berbasis elektrokortikografi telah diujilaksanakan pada pasien dewasa (Vastenseel et al., 2016). Dimasa mendatang, kelompok pasien anak diharapkan dapat memperoleh manfaat dari terobosan teknologi kedokteran tersebut. Beberapa perbedaan karakteristik antara pasien dewasa dan anak membatasi kemungkinan implantasi jangka panjang pasien anak. Solusi bersama ilmu kedokteran dan teknik akan membuka kesempatan dimasa datang bagi implantasi elektroda pada anak.